Intradermal Micro-Dosing of AbobotulinumtoxinA for Face-Lifting: How Long Does It Last? - Rungsima Wanitphakdeedecha (2020)
© 2020, The Author(s). Introduction: Intradermal injection of botulinum toxin type A (BoNT/A) has been used off-label by many clinicians for face-lifting. Previous studies on abobotulinumtoxinA (ABO) (Dysport®; Ipsen Biopharm Ltd.) have demonstrated clinical efficacy in face-lifting when compared to normal saline solution (NSS). However, few clinical studies have evaluated ABO in terms of duration of sustained effects for face-lifting. Methods: Thirty subjects were enrolled, and their face was injected with ABO at a dilution of 1 vial:7 mL (500 U in 7 mL of NSS) using an intradermal injection technique. Standardized photographic documentation was obtained using a two-, and three-dimensional imaging system (Vectra H1, Canfield Scientific, Inc, Fairfield, NJ) at baseline, immediately after injection, 2 weeks after injection and at 1 , 2 , 3 , 4 , 5 and 6 months of follow-up after treatment. The face-lifting effects were graded by both the subjects and two blinded dermatologists who compared photographs taken at the different time points. Side effects were also recorded at the end of the study. Results: Of the 30 subjects, 28 completed treatment and attended every follow-up visit. All subjects were female with Fitzpatrick skin type II to IV. The average age of the subjects was 27.6 ± 3.4 (range 22–34) years. The total number of ABO units used varied for each subject (range 200–250 U), with the average (± standard deviation) dose being 237 ± 19 units. Most of the subjects reported significant face-lifting up to 3 months post-procedure. However, face-lifting assessed by blinded dermatologists was notably lower than that of each patient’s evaluation. The difference in the facial contouring volume of the nasolabial fold and jawline, as measured by the Vectra H1 imaging system, was statistically significant from baseline up until 3 months after injection (p = 0.001 and p = 0.001, respectively). The only side effect found in this study was minimal bruising, which was seen in 13.8% of subjects. None of the subjects reported facial asymmetry, either at rest or during facial expression. Conclusion: The results of this study demonstrate the face-lifting effect of ABO intradermal injection. The results show sustained effects up to 3 months after injection.